The Jäntti Approach to Adsorption with Increasing Gas Pressure - Johannes A. Poulis; Carel H. Massen; Erich Robens (Adsorption Science & Technology)
Jäntti introduced a method of calculating equilibrium adsorption from measurements where the pressure of the gas was varied in a stepwise manner. His aim was to shorten the time necessary for a given measurement. The method was applied to gas/solid systems in which simple adsorption processes occurred and where the number of adsorption sites was infinite. The present paper discusses the case where no adsorption is possible on an already occupied site (Langmuir isotherm) while the number of positions available for adsorption is considered limited. The advantages of using a gas pressure that increases linearly with time are evident for studies with this limitation. It is shown that such measurements can also be speeded up using Jäntti's method.